Estimation of flowering potential and growth pattern on everbearing strawberry Fragaria x ananassa, cv. Favori - Lundblad, Josefine (SLU/Dept. of Plant Protection Biology, 2019)
Flower mapping is a morphological mapping method that can be used in strawberry (Fragaria x ananassa) plant production to get an insight of the status, numbers and the developmental stages of flower buds. It is commonly used by nurseries in order to evaluate plant management techniques to achieve enhanced yield potential over time. In the present study, flower mapping was tested with an everbearing strawberry cultivar Favori in a greenhouse production system. In the trial flower mapping was conducted before planting and after the first harvest on two different batches, planted at two separate dates. This was done to evaluate the applicability of flower mapping on an everbearing cultivar and to gain experience to benefit future production of everbearing strawberries in Sweden. The study showed that the everbearing strawberry cultivar Favori responds to its cultivation system and surrounding environment. The response was expressed as differences in the development pattern and in the plant architecture. To help the interpretation of flower mapping a frequency model was developed summarizing the bud stages and the bud distribution. The flower mapping performed before planting gave an indication of plant quality e.g. number of initiated buds and crown size, and helped to predict future flowering and yield pattern. The second flower mapping conducted after first harvest peak did not predict future flowering pattern, but gave support for the potential future development by identify initiated buds and secondary crowns. In conclusion, flower mapping is suggested to be used as a method to predict potential future inflorescences and to optimize the production of an everbearing strawberry grown in greenhouse.